P157 Sexual Health & Contraception: developing a one stop shop service using a collaborative approach between a Local Authority, Acute and Community Trusts. (30th June 2016) - Whetham, Jenny; Nicholson, Stephen; Fenwick, Vicky; Dean, Gillian
Abstract : Background/introduction: This city on the South East coast has a high proportion of young people/LGBT with some of the highest STI/HIV rates in England (2013 gonorrhoea 162.1/100, 000; HIV prevalence 8/1, 000). GUM & contraception services were historically provided by two separate NHS Trusts. Transfer of public health responsibility to the Local Authority (LA) in 2013 led to service review. Aim(s)/objectives: To deliver an efficient and accessible multi-disciplinary sexual health and contraception service. Methods: City-wide public consultation favoured a one-stop-shop integrated service. Pathway Analytics© sexual health tariff was accepted by LA/providers as a transparent & fair payment mechanism. Following legal advice LA gave the commissioner permission to negotiate a new contract with existing providers, moving to a competitive tender process if unsuccessful. Results: The contract was awarded to existing providers in April 2015. The local Sexual Health Programme Board ensured all stakeholders were engaged in service review. A staged approach was followed to deliver an integrated service. The tariff was introduced allowing fair remuneration for combined services at diverse sites across the city. Trusts have established a steering group to ensure safe governance across legal, financial & clinical frameworks & robust risk management processes across both organisations. Discussion/conclusion: Innovative thinking by the LA allowed service re-design by negotiation with existing providers avoiding a competitive tender process. Good working relationships within the sexual health network allowed a collaborative approach to service improvement. Despite the challenges of two Trusts working together with different organisational accountabilities, a 'one-stop-shop model' has been successfully introduced without destabilising HIV services.